2006
DOI: 10.1002/hep.21381
|View full text |Cite
|
Sign up to set email alerts
|

Impaired 11β‐hydroxysteroid dehydrogenase contributes to renal sodium avidity in cirrhosis

Abstract: Exaggerated renal sodium retention with concomitant potassium loss is a hallmark of cirrhosis and contributes to the accumulation of fluid as ascites, pleural effusion, or edema. This apparent mineralocorticoid effect is only partially explained by increased aldosterone concentrations. I present evidence supporting the hypothesis that cortisol confers mineralocorticoid action in cirrhosis. The underlying molecular pathology for this mineralocorticoid receptor (MR) activation by cortisol is a reduced activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Because chenodeoxycholic acid is increased in cholestasis and dosedependently inhibits 11␤-HSD2 activity in CCD allowing activation of the MR by endogenous corticosterone, 29,48 this pathway was proposed as the initial stimulator of sodium retention during liver cirrhosis. 32,49,50 However, present data in corticosteroid-clamped BDL mice demonstrate that inhibition of 11␤-HSD2 activity is not essential for sodium retention in liver cirrhosis. First, activation of MR should stimulate Na ϩ ,K ϩ -ATPase and induce over-expression of sgk1 and ENaC mRNAs all along the distal nephron and not specifically in the CCD.…”
Section: Discussionmentioning
confidence: 54%
“…Because chenodeoxycholic acid is increased in cholestasis and dosedependently inhibits 11␤-HSD2 activity in CCD allowing activation of the MR by endogenous corticosterone, 29,48 this pathway was proposed as the initial stimulator of sodium retention during liver cirrhosis. 32,49,50 However, present data in corticosteroid-clamped BDL mice demonstrate that inhibition of 11␤-HSD2 activity is not essential for sodium retention in liver cirrhosis. First, activation of MR should stimulate Na ϩ ,K ϩ -ATPase and induce over-expression of sgk1 and ENaC mRNAs all along the distal nephron and not specifically in the CCD.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, recent observations have indicated that a key contribution results from alterations in the enzymatic clearance of cortisol. In liver disease, inactivation of cortisol by the enzymes 5β-reductase ( Akr1d1 ) and 11β-hydroxysteroid dehydrogenase type 2 ( Hsd11b2 ; Frey 2006, McNeilly et al . 2010) is impaired.…”
Section: Introductionmentioning
confidence: 99%
“…p38 mitogen-activated protein kinase; chromatin immunoprecipitation; RNA interference IN MAMMALIAN TISSUES, THE SENSITIVITY to glucocorticoids depends not only on circulating glucocorticoid levels, but also on glucocorticoid receptor expression and intracellular availability of active glucocorticoid, which is determined by 11␤-hydroxysteroid dehydrogenase enzymes (11␤-HSD) (21,22). Two enzymes play a role in this process, 11␤-HSD1 and 11␤-HSD2.…”
mentioning
confidence: 99%